Metodología para el estudio de los tejidos biológicos usando matrices de Mueller - Martínez-Celorio, R. A.; Espinosa-Luna, Rafael; Rivera-Vázquez, J. O.; Castro-Sánchez, R. (Revista Mexicana de Ingenieria Biomedica, 2006)
A methodology for the study of the biological tissues by means of the matrixes of Mueller is proposed. The methodology is based on obtaining the fundamental differences among the elements of the matrix of Mueller corresponding to two samples of biological tissues, one of the breast and the other a man thorax tissue. Each element of the matrix is obtained by using an optic arrangement that consists of Angular Resolution Scattering, which is robust and simple of implementing. The obtained results show differences among the elements of the matrix of Mueller of each tissue. The advantages and disadvantages are discussed.